Retraction notice: Influence of compressing pressure on macro void formation carbon monolith for methane adsorption - B, Narandalai; Shim, W G; Balathanigaimani, M S; Moon, H (Mongolian Journal of Chemistry, 2019)
RETRACTION NOTICE On 21rd February 2019, the Editorial Board of the Mongolian Journal of Chemistry decided to retract this article entitled "Influence of compressing pressure on macro void formation of carbon monolith for methane adsorption" because of an authorship dispute. The article was originally published in Vol.18 No.44 2017 pp.24-35. doi: https://doi.org/10.5564/mjc.v18i44.934